Antagonist yeast for biocontrol of postharvest anthracnose disease on papaya (Carica papaya L.) - Hassan, Hamizah (2017)
Papaya (Carica papaya L.) contain high nutritive value and very susceptible to postharvest decay. Major postharvest disease related to papaya fruit is anthracnose, caused by Colletotrichum gloeosporioides. Postharvest fungicide treatments are very popular for the disease control due to it fast and broad spectrum effects. However, withdrawal of a few commercial fungicides due to its negative effects on human, environment and produce increased public concerns and demands to other safer alternatives of control measures. Among all, biological control using microorganism to fight against host pathogens provides a positive results. However, limited studies done in Malaysia regarding the use of yeast as biocontrol agent for postharvest disease. Thus, this study was carried out with aim to develop a locally isolated, yeast antagonist agent for controlling anthracnose disease on papaya. In the first experiment, isolation of natural yeast on papaya plant was carried out. A total of 110 yeasts were isolated and tested for their antagonist activity against C. gloeosporioides. After a series of initial screening tests for antagonism, two yeasts, namely F001 and FL013 showed higher antagonistic activity against the pathogen were selected. Both F001 and FL013 showed better antagonist activity when concentration of yeast cells were increased from 5 x 104 to 5 x 108 cells mL-1 in fungal spore germination test. Both yeasts also showed their ability to work well in cold storage condition and significantly inhibited the mycelial growth up to 70% using FL013 dipping treatment. However, only F001 has the ability to produce diffusible antifungal compounds which caused total suppression (100%) on the fungal growth. Thus, by referring to previous results, only F001 was identified and used in next experiments. Yeast F001, identified as Trichosporon asahii, also exhibited direct attachment on pathogen to control fungal hyphae growth and able to colonize well on papaya peel. In the next experiment, suitable additives for combining with T. asahii to improve antagonist activity of the yeast was investigated. Results showed that combination of T. asahii with calcium chloride able to totally suppress the pathogen growth in in vitro test. For in vivo test, combination of T. asahii with calcium chloride at 2.5% (w/v) caused reduction in disease severity until 83% as compare to control fruit. This treatment combination was chosen and used in the subsequent studies. Next, effect of utilizing this treatment combination on disease incidence, disease severity, total phenolic, total flavonoid and antioxidant activity were evaluated. Results showed that T. asahii with 2.5% calcium chloride coating on ‘Solo’ papaya was capable to reduce disease severity but not able to significantly increase the activity of those phytochemicals. The treatment also showed that no interaction effect with storage day on defense-related enzyme, including polyphenol oxidase, phenylalanine ammonia lyase and catalase activity. However, treatment application on the fruit did not influence the quality and storability of papaya after stored at 12 °C for 28 days.